Let Us Dance. (September 2017) - Fitzpatrick, Esther; Worrell, Frank C.; Alansari, Mohamed; Yang Li, Alex
I looked at the call for papers, "Poetic responses to Orlando" and paused. Should I contribute? And then I thought, how could I hide in the safety of my so-called normality and straightness when others may have become afraid to dance? So I invited my friends to join me in a poetic response.